Anatomical and histological descriptions of digestive canal and excretory system of Mylabris cernyi Pan & Bologna, 2014 (Coleoptera: Meloidae). (3rd July 2022) - Özyurt Koçakoğlu, Nurcan; Candan, Selami; Güllü, Mustafa
ABSTRACT: In the present study, we described the histological and anatomical studies of the digestive canal and excretory system of Mylabris cernyi with light and scanning electron microscopies. The digestive canal is divided into three parts: the foregut, the midgut, and the hindgut. The foregut includes a pharynx, an oesophagus, a proventriculus and an oesophageal valve. There are the muscle layer, a thin epithelium, and the intima lining in the parts of the foregut. The midgut is well developed and has a transversely wrinkled shape. This epithelial layer of columnar cells is invaginated to form large and deep folds of epithelial tissue. The hindgut has pyloric valve, ileum, colon, and rectum. In the cell layers of the hindgut, there is an inner lining of the intima of cuticula, an epithelial layer and a muscle layer. There are 6 Malpighian tubules which are attached between the midgut and the hindgut. The results will help guide the development of new strategies for managing this pest. Because knowing the fine structure of the digestive and excretory system of this species is important in terms of forming the basis for the studies to be carried out in agricultural control against this species.